2023
DOI: 10.1167/tvst.12.8.5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Carboxymethylcellulose Artificial Tears on Ocular Surface Microbiome Diversity and Composition, A Randomized Controlled Trial

Abstract: Purpose Carboxymethylcellulose is an artificial tear ingredient known to decrease gut microbiome diversity when ingested. This study examines the effect of carboxymethylcellulose on ocular surface microbiome diversity and composition. Methods Healthy adult participants without significant ophthalmic disease or concurrent carboxymethylcellulose artificial tear use were allocated randomly to take carboxymethylcellulose or control polyethylene glycol artificial tears for s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…A randomized trial comparing Carboxymethylcellulose to Polyethylene Glycol artificial tears found specific changes at genus level, including an increase in Bacteroidota and Actinobacteriota with Carboxymethylcellulose treatment [ 58 ]. However, overall diversity of the OSM was not significantly altered by these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…A randomized trial comparing Carboxymethylcellulose to Polyethylene Glycol artificial tears found specific changes at genus level, including an increase in Bacteroidota and Actinobacteriota with Carboxymethylcellulose treatment [ 58 ]. However, overall diversity of the OSM was not significantly altered by these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism of action of CMC is not yet fully understood, it has been shown that its high micro-viscosity allows it to bind to human corneal epithelial cells [12], improving the ocular protection index for at least 20 min after instillation [21]. In addition, CMC also reduces the enrichment of Firmicutes bacteria [22], which have been associated with MGD and, therefore, a reduced LLT [22,23]. This is consistent with our results, which seem to be higher than those reported by the aforementioned studies that used 0.5% CMC tear substitute treatment.…”
Section: Carboxymethylcellulose Efficacymentioning
confidence: 99%
“…CMC mimics the muco-mimetic properties of natural mucin found in the tear film, thus aiding in moisture retention and corneal epithelium healing [12,21]. In addition, CMC may also reduce the enrichment of Firmicutes bacteria, which is associated with MGD [22,23]. Recent innovations, such as preservative-free CMC tear substitutes, have expanded the scope of its application, significantly reducing the toxic effects commonly associated with preservatives in ophthalmic solutions [19].…”
Section: Introductionmentioning
confidence: 99%